Islam in Madurese’s Cosmological Interpretation: Structural Analysis of Tanean Lanjeng in Madura - Zuhri Humaidi (Institut Agama Islam Negeri Madura, 2020)
Madurese are known as devout Muslims. Islam and Madurese culture are two integrated identities like two sides of a coin. Islam and Madurese culture shape the value, word view and culture of Madurese people. Then, how significance are these two aspects in its cosmological order? What is Madurese’s cognitive structure in interpreting their world and forming a material culture? These questions are problems that will be revealed in this paper through research on Tanean Lanjeng, which is a typical settlement pattern in Madura. With Levi Strauss's structuralism approach, Tanean Lanjeng is seen as a code of conduct from the cognitive structure of the Madura people who formulate their ideas and actions. Tanean Lanjeng is a surface structure of a culture while the cognitive aspect is a deep structure. This paper further elaborates that the tanean lanjeng settlements in Madura not only have practical and social functions but show certain meanings that reflects the thinking and worldview of the Madurese. Values such as the equality of male and female relations, strong kinship ties, respect for certain figures, and Islam that are so deeply rooted in a structure that determines how Madurese behave, shape culture and interpret the world around them.